Environmental Assessment Using Phytoplankton Diversity, Nutrients, Chlorophyll-a, and Trophic Status Along Southern Coast of Jeddah, Red Sea - Bandar A. Al-Mur (Journal of Marine Science and Engineering)
The objective of this study is to better identify the state of eutrophication of coastal waters along the southern coast of the city of Jeddah in the Red Sea. Thirty-six samples from surface seawater were collected during the spring and autumn of 2021. Water temperature, pH, salinity, dissolved oxygen (DO), nutrients, and chlorophyll-a (Chl-a) content were examined as a guide of water quality indicators. The present data revealed low levels of Chl-a content (in the range of 0.11–0.24 µg L−1). The average concentrations of DIN (dissolved inorganic nitrogen) forms follow the order NO3-N > NH4-N ~ NO2-N (representing about 11.4–29.4% of the total nitrogen). To investigate the trophic status and water quality, numerical indicators were applied to the results of the analysis of chemical variables (NH4-N, NO3-N, and PO4-P) and the biological analysis (Chl-a) in the aqueous environment within the study area. These indicators are simplified based on the specialist, the non-specialist, the decision-maker, and the one responsible for managing the coastal areas. We also obtain through this method a single numerical value that expresses the state of the coastal waters. According to the analysis of phosphorus and nitrogen data and a trophic index (TRIX), the study area’s trophic status was determined as oligotrophic, due to low nutrient concentrations in the seawater. The current study identified a total of 58 species of phytoplankton comprised four classes in the investigated areas; Bacillariophyceae was the dominant algal class (Diatoms 30 species), followed by Chlorophyceae (9 species), Dinophyceae (11 species), and Cyanophyceae (8 species). Seasonally, spring recorded the highest value of total phytoplankton, recording a value of 251 × 103 cells/L with a percentage of 61%, while autumn recorded the lowest value of 186 × 103 cells/L with a percentage of 39%. Phytoplankton classes can be arranged in order of prevalence as follows: Bacillariophyceae >> Dinophyceae > Chlorophyceae > Cyanophyceae.